1990
DOI: 10.1093/jnci/82.10.840
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Mortality in the U.S. Flour Industry

Abstract: The mortality experience among 22,938 white males who were enrolled in the life insurance program of the American Federation of Grain Millers was assessed for the period 1955 through 1985 in a cohort mortality analysis and in a nested case-control analysis. Significantly fewer deaths were observed among this group than expected for all causes of death combined [standardized mortality ratio (SMR) = 89] compared with the number of deaths observed among the general population of U.S. white males of the same age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 0 publications
2
29
0
1
Order By: Relevance
“…An exploratory study by Friedman and van den Eeden (1993) found a small, significant risk for pancreas cancer in people who had used insect or plant sprays earlier than 1 year before they were interviewed, but information on the type of pesticides used was not gathered. Three occupational studies found a significant excess of pancreas cancer in workers handling pesticides (Kauppinen et al, 1995), workers employed in flour mills (Alavanja et al, 1990) and nurserymen (Milham, 1983). Workers in all of these studies had the potential for extensive insecticide exposures, but, similar to the study of Friedman and van den Eeden (1993), information on specific pesticide exposures was not available in any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…An exploratory study by Friedman and van den Eeden (1993) found a small, significant risk for pancreas cancer in people who had used insect or plant sprays earlier than 1 year before they were interviewed, but information on the type of pesticides used was not gathered. Three occupational studies found a significant excess of pancreas cancer in workers handling pesticides (Kauppinen et al, 1995), workers employed in flour mills (Alavanja et al, 1990) and nurserymen (Milham, 1983). Workers in all of these studies had the potential for extensive insecticide exposures, but, similar to the study of Friedman and van den Eeden (1993), information on specific pesticide exposures was not available in any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alavanja et al 113 reported no associations among flour mill (SMR 5 0.98) or other grain industry workers (SMR 5 1.01) with suspected pesticide exposure.…”
Section: Italymentioning
confidence: 98%
“…Positive associations were reported among USDA forest (OR 5 2.5, 95% CI: 1.0-6.3) and soil (OR 5 1.8, 95% CI: 0.7-4.1) conservationists. 125 Alavanja et al 128,124 reported no significant excess mortality among white male grain industry workers (proportionate mortality ratio There were no reported deaths due to lymphatic or hematopoietic neoplasms among 1,261 veterans in Operation Ranch Hand, the unit responsible for aerial herbicide spraying operations and presumably the group in Vietnam most highly exposed to dioxins. 122 Ranch Hands were reported to have 3-fold higher serum TCDD levels than non-herbicide spraying Air Force comparison subjects.…”
Section: Occupational and Environmental Factors Occupational And Envimentioning
confidence: 99%